Sharpening your advanced SAS skills - Gupta, Sunil 1963- (CRC Press, 2016)
Sharpening Your Advanced SAS® Skills presents sophisticated SAS programming techniques, procedures, and tools, such as Proc SQL, hash tables, and SAS Macro programming, for any industry. Drawing on his more than 20 years'experience of SAS programming in the pharmaceutical industry, the author provides a unique approach that empowers both advanced programmers who need a quick refresher and programmers interested in learning new techniques. The book helps you easily search for key points by summarizing and differentiating the syntax between similar SAS statements and options. Each chapter begins with an overview so you can quickly locate the detailed examples and syntax. The basic syntax, expected data, and descriptions are organized in summary tables to facilitate better memory recall. General rules list common points about similar statements or options. Real-world examples of SAS programs and code statements are line numbered with references, such as SAS papers and websites, for more detailed explanations. The text also includes end-of-chapter questions to reinforce your knowledge of the topics and prepare you for the advanced SAS certification exam. In addition, the author's website offers mindmaps and process flowcharts that connect concepts and relationships.
Includes bibliographical references. - Print version record
Keywords: SAS (Computer file); Mathematical statistics -- Data processing; Statistique mathématique; Informatique; MATHEMATICS; Applied; MATHEMATICS; Probability & Statistics; General; Mathematical statistics; Data processing